Smart prayer mat - Amir, Ahmed; Htike@Muhammad Yusof, Zaw Zaw (Centre for Islamisation (CENTRIS), 2016)
as the Qiblah. There is a need to determine the Qiblah. Using a compass is a feasible technique. However, for places that are not exactly north, south, east or left of Kaaba, this is not a straightforward task. Furthermore, there are elderly people with memory impairment and people suffering from short-term memory disorders and dementia. They cannot keep track of how many Rakaats have been performed. Therefore, they cannot pray when they are alone at home. This chapter describes a project called smart prayer mat that has a built-in mechanism to determine the Qiblah and keeps track of the number of Rakaats using light emitting diodes. The prayer mat determines its location using a GPS receiver and then calculates the Qiblah. When the direction of the mat is aligned to the true direction of the Qibat within a reasonable level of threshold, the prayer mat lights up. There are also light emitting diodes of a different color that light up in accordance with how many Rakaat the user has performed. The smart prayer mat achieves this by counting the number of Sujud using a pressure sensitive sensor. The count resets itself at the end of the Solat.